2002
DOI: 10.1074/jbc.m206588200
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Regulation of Cystathionine β-Synthase Expression in Liver

Abstract: Homocysteine metabolism is altered in diabetic patients. Cystathionine ␤-synthase (CBS), a key enzyme involved in the transsulfuration pathway, which irreversibly converts homocysteine to cysteine, catalyzes the condensation of serine and homocysteine to cystathionine. Studies in streptozotocin-induced diabetic rats have shown that CBS enzyme activity is elevated in the liver but not in the kidney, and this effect is reversed by insulin treatment. To determine whether these effects resulted from alterations at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
130
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(148 citation statements)
references
References 50 publications
15
130
1
2
Order By: Relevance
“…The level of hepatic cystathionine ␤-synthase, a transmethylation enzyme that metabolizes conversion of homocysteine to cystathione (36), was elevated and plasma homocysteine reduced in untreated, insulin-deficient diabetic rats, and the defects were normalized by treatment with insulin. Furthermore, cystathionine ␤-synthase mRNA levels were markedly elevated in streptozotocininduced diabetic rat livers and reduced by insulin administration (37). Considering that insulin resistance may be an expression of diffuse arterial endothelial dysfunction, which contributes to atherosclerosis directly or indirectly (38), it is not surprising that these two risk factors are associated with cardiovascular disease.…”
Section: Resultsmentioning
confidence: 99%
“…The level of hepatic cystathionine ␤-synthase, a transmethylation enzyme that metabolizes conversion of homocysteine to cystathione (36), was elevated and plasma homocysteine reduced in untreated, insulin-deficient diabetic rats, and the defects were normalized by treatment with insulin. Furthermore, cystathionine ␤-synthase mRNA levels were markedly elevated in streptozotocininduced diabetic rat livers and reduced by insulin administration (37). Considering that insulin resistance may be an expression of diffuse arterial endothelial dysfunction, which contributes to atherosclerosis directly or indirectly (38), it is not surprising that these two risk factors are associated with cardiovascular disease.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that the cystathionine b-synthase (CBS) enzyme, which is involved in H 2 S generation using cysteine and homocysteine as sulphide sources, is strongly expressed in nonconfluent HepG2 cells, but the activity of CBS is significantly decreased after the cells are treated with human insulin [49][50][51][52] . Thus, we adopted normal and insulin-pretreated HepG2 cells as model cells, incubated them with the PNPs, and examined whether variations in intracellular H 2 S production could be detected.…”
Section: Resultsmentioning
confidence: 99%
“…This shift is also reflected in other 270 gluconeogenic states, such as diabetes. We and others have demonstrated that a diabetic state or 271 administration of synthetic glucocorticoid compounds has a major impact on methyl group and 272 homocysteine metabolism [23][24][25][26][49][50][51][52]. A consistent finding from these reports is a reduction 273 in circulating homocysteine concentrations owing to an increase in folate-independent 274 remethylation (i.e., BHMT) and catabolism of homocysteine through the transsulfuration 275 pathway.…”
mentioning
confidence: 88%